Evaluation of Adiponectin, Irisin, Vitamin D Levels and Their Relation in Iraqi Patients with Non alcoholic Fatty Liver Disease - Abdul Sattar , Alaa; T. AL-Sa'adi, Warka'a (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Non-alcoholic fatty liver disease (NAFLD) is one of chronic liver and defines by fat accumulation ≥5% in liver which can progresses to non-alcoholic steatohepatitis (NASH). NAFLD related to obesity as well as non obese individuals. Adiponectin is a cytokine secreted from adipose tissue involved NAFLD pathogenesis and liked with obesity. Irisin is a myokine, has a convenient effect against metabolic diseases such as obesity, disylipemia diabetes type 2 and reversed liver steatosis and may be related with NAFLD. Vitamin D is one of the fat soluble vitamins and more precisely as a pro-hormone through its metabolite (1,25(OH)2 cholecalciferol) the major steroid hormone. After the skin exposure to the light, vitamin D undergoes to activation through two successive hydroxylation reactions in liver and kidney. Several metabolic diseases such as dyslipidaemia, obesity, hypertension, T2D and metabolic syndrome (MS) have been related to vitamin D deficiency.